Phase-Dependent Crossed Inhibition Mediating Coordination of Anti-phase Bilateral Rhythmic Movement: A Mini Review - Hiraoka, Koichi (Frontiers in Human Neuroscience, 2021)
Activity of the left and right central pattern generators (CPGs) is efficiently coordinated during locomotion. To achieve this coordination, the interplay between the CPG controlling one leg and that controlling another must be present. Previous findings in aquatic vertebrates and mammalians suggest that the alternate activation of the left and right CPGs is mediated by the commissural interneurons crossing the midline of the spinal cord. Especially, V0 commissural interneurons mediate crossed inhibition during alternative activity of the left and right CPGs. Even in humans, phase-dependent modulation of the crossed afferent inhibition during gait has been reported. Based on those previous findings, crossed inhibition of the CPG in one leg side caused by the activation of the contralateral CPG is possible mechanism underlying the coordination of the anti-phase rhythmic movement of the legs. It has been hypothesized that the activity of the flexor half center in the CPG inhibits the contralateral flexor half center, but crossed inhibition of the extensor half center is not present because of existence of the double limb support during gait. Nevertheless, previous findings on the phase-dependent crossed inhibition during anti-phase bilateral movement of the legs are not in line with this hypothesis. For example, extensor activity caused crossed inhibition of the flexor half center during bilateral cycling of the legs. In another study, the ankle extensor was inhibited at the period switching from extension to flexion during anti-phase rhythmic movement of the ankles.